Student Perceptions of Effective Teaching Traits and Strategies (Journal on Excellence in College Teaching, 2024)
The purpose of this study was to examine differences in student perceptions of instructor and course characteristics for courses that students deemed to be high in learning versus high in enjoyment. Realizing that students differ from faculty in how they view the traits of a highly effective instructor, the authors created a survey of student perceptions of effective teaching traits and strategies. After administering the survey to 315 undergraduate students across multiple disciplines, they discovered a basic variation between faculty and student perceptions. In both types of courses (high-learning and high-enjoyment), students stated that the instructors’ interpersonal (soft) skills were highly prevalent. Recommendations are made for promoting soft skills among instructors to foster both learning and enjoyment among students.